2017
DOI: 10.1161/jaha.117.007207
|View full text |Cite
|
Sign up to set email alerts
|

Nativity Status and Cardiovascular Disease Mortality Among Hispanic Adults

Abstract: BackgroundHispanic persons represent a heterogeneous and growing population of any race with origins in Mexico, the Caribbean, Central America, South America, or other Spanish‐speaking countries. Previous studies have documented variation in cardiovascular risk and outcomes among Hispanic subgroups. Few studies have investigated whether these patterns vary by nativity status among Hispanic subgroups.Methods and ResultsWe used the National Center for Health Statistics mortality file to compare deaths of Hispani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Our meta-analysis included studies published between January, 2001, and March, 2017. We updated our search from March 31, 2017, to Sept 3, 2018, which yielded ten additional papers49, 50, 51, 52, 53, 54, 55, 56, 57, 58 that met our inclusion criteria that had been published since the original search. Of these ten studies, nine were done in high-income countries (two from the same dataset in Belgium), and were focused on international migrants with no disaggregation by subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis included studies published between January, 2001, and March, 2017. We updated our search from March 31, 2017, to Sept 3, 2018, which yielded ten additional papers49, 50, 51, 52, 53, 54, 55, 56, 57, 58 that met our inclusion criteria that had been published since the original search. Of these ten studies, nine were done in high-income countries (two from the same dataset in Belgium), and were focused on international migrants with no disaggregation by subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…We measured nativity with a dichotomous indicator of whether the person was born in any of the 50 states or outside of the US. Although Puerto Rico is a US territory, Puerto Ricans born in the island do not consider themselves to be “US‐born” and generally have a different health profile than those born in the mainland US . Therefore, we considered Puerto Ricans born outside the US as “non‐US‐born.” A total of 78 individuals identified as “other” race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…Nativity status was not considered in this study because the numbers of U.S. born Hispanics are small for Cubans and Central or South Americans. However, studies have shown there are significant differences between foreign-born and U.S. born Hispanic cancer burden for most cancer sites (14,45,46). The study also did not account for racial differences between Hispanic Whites and Hispanic Blacks.…”
Section: Limitationsmentioning
confidence: 87%